2018
DOI: 10.1038/s41598-018-32428-9
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of Skp2 expression inhibits invasion and lung metastasis in osteosarcoma

Abstract: Osteosarcoma (OS), the most common primary cancer of bone, exhibits a high propensity for local invasion and distant metastasis. This study sought to elucidate the role of S phase kinase-associated protein (Skp2) in osteosarcoma invasion and metastasis and to explore flavokawain A (FKA), a natural chalcone from kava extract, as a potential Skp2 targeting agent for preventing osteosarcoma progression. Skp2 was found to be overexpressed in multiple osteosarcoma cell lines, including 5 standard and 8 primary pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
69
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(72 citation statements)
references
References 47 publications
3
69
0
Order By: Relevance
“…Furthermore, SKP2 has also been proven to enhance tumor invasion ability by promoting epithelial-mesenchymal transition (EMT) process and matrix metalloproteinase (MMP) expression [37,38] . Based on these encouraging results, Zhang et al found knockdown of Skp2 could result in RhoA and MMP-9 inhibition, thereby signi cantly reducing tumor cell invasion and lung metastasis in an orthotopic mouse model of osteosarcoma [39] . Not only that, SKP2 has also been reported to exert an effect in DNA damage response, DNA repair, tumor angiogenesis and drug resistance [40,41] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, SKP2 has also been proven to enhance tumor invasion ability by promoting epithelial-mesenchymal transition (EMT) process and matrix metalloproteinase (MMP) expression [37,38] . Based on these encouraging results, Zhang et al found knockdown of Skp2 could result in RhoA and MMP-9 inhibition, thereby signi cantly reducing tumor cell invasion and lung metastasis in an orthotopic mouse model of osteosarcoma [39] . Not only that, SKP2 has also been reported to exert an effect in DNA damage response, DNA repair, tumor angiogenesis and drug resistance [40,41] .…”
Section: Discussionmentioning
confidence: 99%
“…Due to the extensive carcinogenic effects of SKP2, research on the anti-tumor activity of SKP2 small molecule inhibitors is in full swing. Among them, avokawain A (FKA), an effective apoptotic inducer and antiproliferative agent in the tumor, which could lead to down-regulation of SKP2, result in osteosarcoma growth retardation and metastasis inhibition [39] . However, more preclinical and clinical trials are necessary to explore the application of the speci c SKP2 inhibitors in the treatment of osteosarcoma with lung metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports have documented the anticancer activity of chalcone-based flavokavain A in various cancer cell culture models. For example, flavokavain A was reported to inhibit cancer progression in taxol-resistant cancer cells [ 119 ], inhibit cancer cell proliferation and metastasis [ 120 ], and induce apoptosis [ 121 ], autophagy, and G2/M cell cycle arrest [ 22 , 122 , 123 ]. It was also reported to enhance antitumor immunity [ 124 ] and synergize with chemotherapies [ 125 ].…”
Section: Kava and Cancermentioning
confidence: 99%
“…It suppressed bladder cancer (T24) growth in a xenograft mouse model (50 mg/kg/d) [ 121 ]. At 200 mg/kg/d, flavokavain A inhibited lung metastasis of osteosarcoma cells in mice potentially via reducing Skp2 expression [ 120 ]. Lastly, flavokavain A was reported to enhance antitumor immunity and suppress the inflammatory process in breast cancer-challenged mice (50 mg/kg/d) [ 124 ].…”
Section: Kava and Cancermentioning
confidence: 99%
“…An increase in p27 Kip1 has been found to significantly reduce Mixed-Lineage Leukemia self-renewal ability, promote the monocytic differentiation of leukemic blasts, and induce cell death [5]. Skp2 has shown important roles in the development and progression of tumors as it was found to be frequently overexpressed in various human malignancies like hepatocellular carcinoma, breast cancer, lung cancers, prostate cancer, and osteosarcoma [2,[6][7][8][9][10][11]. In hepatocellular carcinoma, Skp2 was identified at a significantly increased level compared with paired normal tissue, and was correlated with tumor grade, size, and metastases.…”
Section: Introductionmentioning
confidence: 99%